A Distinct Pathway for Polar Exocytosis in Plant Cell Wall Formation . Issue 2 (16th August 2016) - Wang, Hao; Zhuang, Xiaohong; Wang, Xiangfeng; Law, Angus Ho Yin; Zhao, Teng; Du, Shengwang; Loy, Michael M.T.; Jiang, Liwen
Abstract : A distinct Golgi-derived polar exocytosis pathway occurs in Nicotiana tabacum for pectin methylesterase 1 and contributes to cell wall and cell plate formation during cytokinesis. Abstract: Post-Golgi protein sorting and trafficking to the plasma membrane (PM) is generally believed to occur via the trans-Golgi network (TGN). In this study using Nicotiana tabacum pectin methylesterase (NtPPME1) as a marker, we have identified a TGN-independent polar exocytosis pathway that mediates cell wall formation during cell expansion and cytokinesis. Confocal immunofluorescence and immunogold electron microscopy studies demonstrated that Golgi-derived secretory vesicles (GDSVs) labeled by NtPPME1-GFP are distinct from those organelles belonging to the conventional post-Golgi exocytosis pathway. In addition, pharmaceutical treatments, superresolution imaging, and dynamic studies suggest that NtPPME1 follows a polar exocytic process from Golgi-GDSV-PM/cell plate (CP), which is distinct from the conventional Golgi-TGN-PM/CP secretion pathway. Further studies show that ROP1 regulates this specific polar exocytic pathway. Taken together, we have demonstrated an alternative TGN-independent Golgi-to-PM polar exocytic route, which mediates secretion of NtPPME1 for cell wall formation during cell expansion and cytokinesis and is ROP1-dependent.